Peptides vs. Polymers: Searching for the Most Efficient Delivery System for Mitochondrial Gene Therapy - Rúben Faria; Milan Paul; Swati Biswas; Eric Vivès; Prisca Boisguérin; Ângela Sousa; Diana Costa (Pharmaceutics, 2022)
Together with the nucleus, the mitochondrion has its own genome. Mutations in mitochondrial DNA are responsible for a variety of disorders, including neurodegenerative diseases and cancer. Current therapeutic approaches are not effective. In this sense, mitochondrial gene therapy emerges as a valuable and promising therapeutic tool. To accomplish this goal, the design/development of a mitochondrial-specific gene delivery system is imperative. In this work, we explored the ability of novel polymer- and peptide-based systems for mitochondrial targeting, gene delivery, and protein expression, performing a comparison between them to reveal the most adequate system for mitochondrial gene therapy. Therefore, we synthesized a novel mitochondria-targeting polymer (polyethylenimine–dequalinium) to load and complex a mitochondrial-gene-based plasmid. The polymeric complexes exhibited physicochemical properties and cytotoxic profiles dependent on the nitrogen-to-phosphate-group ratio (N/P). A fluorescence confocal microscopy study revealed the mitochondrial targeting specificity of polymeric complexes. Moreover, transfection mediated by polymer and peptide delivery systems led to gene expression in mitochondria. Additionally, the mitochondrial protein was produced. A comparative study between polymeric and peptide/plasmid DNA complexes showed the great capacity of peptides to complex pDNA at lower N/P ratios, forming smaller particles bearing a positive charge, with repercussions on their capacity for cellular transfection, mitochondria targeting and, ultimately, gene delivery and protein expression. This report is a significant contribution to the implementation of mitochondrial gene therapy, instigating further research on the development of peptide-based delivery systems towards clinical translation.